Enhancing Students’ Learning Motivation through Responsive Ice-Breaking Activities in Islamic Religious Education: Quasi-Experimental Evidence from Indonesian Senior High School - Elbina Mamla Saidah; Intan Muliani; Wiwid Hadi Sumitro; Khairul Amin; Mariatul Hikmah (CV. Edujavare Publishing, 2026)
Learning motivation in Islamic Religious Education and Character Building often declines when classroom instruction relies heavily on one-way explanation and offers limited space for student participation. This study examined the effect of responsive ice-breaking activities on students’ learning motivation at SMA Negeri 5 Mandau, Indonesia. A quantitative quasi-experimental design with a non-equivalent control group was used. The participants were 58 tenth-grade students, consisting of 30 students in the experimental group and 28 students in the control group. The experimental group received Islamic Religious Education lessons integrated with responsive ice-breaking activities, while the control group followed regular instruction. Data were collected using a learning motivation questionnaire and documentation, and were analyzed through descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, and an independent-samples t-test. The study was informed by Self-Determination Theory and the ARCS motivational model. The results showed that the experimental group achieved a higher post-test mean score than the control group. The t-test confirmed a significant difference between groups, t(56) = -2.589, p = .012, with a moderate effect size. These findings suggest that responsive ice-breaking activities can help restore students’ attention, reduce classroom fatigue, and support learning motivation during Islamic Religious Education lessons.